(untitled) (Journal of Plant Disease Sciences, 2024)
The present study deals with the detection, identification, estimation of mycoflora associated with pigeon pea seeds Fusarium, Phytophthora, Alternaria, Rhizoctonia and Cercospora are the most common fungal pathogen associated with stored seed and aremainly responsible for seed deterioration, reduction in germination potential and seedling. Hence, the present study investigated seed samples of pigeon pea variety, PKV-TARA collected from Pulse Research Unit, Dr. PDKV, Akola (Maharashtra) were tested for the detection and identification of seed borne mycoflora by various methods viz., standard blotter paper method, agar plate method, rolled paper towel method.